Analysis of Qt libraries usage in selected interprocess communication aplications - Górniak, Łukasz Janusz; Pańczyk, Maciej (Journal of Computer Sciences Institute, 2017)
This article illustrates what Qt is. An example of the producer-consumer problem implementation in interprocess communication based on the shared memory is presented. Such solution can simplify the process of building interprocess application for those who want to write their programs using Qt in all possible aspects.